New species of Trichomycterus (Siluriformes: Trichomycteridae) from the High Andean Plateau of Argentina - Fernández, Luis; Bize, Julieta Andreoli (Zootaxa, 2018)
Trichomycterus varii new species, is described from a small tributary of the High Andean Plateau Region, Jujuy, Argentina. The new species is distinguished from other species of Trichomycterus by the following characters: the caudal peduncle expanded in the area of procurrent caudal-fin rays, distal tip of pelvic fin not reaching the anus when depressed, the presence of fronto-lachrymal tendon bone without lateral process, the first pectoral-fin ray terminating at the margin of the fin, the distal margin of pectoral-fin rounded, seven pectoral fin rays, 15–19 interopercular odontodes, the supraorbital sensory canal with the presence of pore s3, the infraorbital sensory canal segment with the presence of pores i1 and i3, the laterosensory canal of trunk with three sensory pores, 16 pairs of ribs, 11 precaudal vertebrae, and 25 caudal vertebrae. It closely resembles T. yuska and T. pseudosilvinichthys from northwestern Argentina and western Bolivia, but differs in head canal sensory pattern.